MODERASI ISLAM: Untuk Peradaban dan Kemanusiaan - Sudarji, Sudarji (LP. Ma'arif Janggan Magetan, 2020)
Abstract: Islam is inseparable from al-Qur'an and al-Hadith as a source of legal resources. But on the other hand, Islam is stigmatized as an extreme religion, in the name of religion originating from the Qur'an and as-Sunnah. This study aims to describe and track the moderation of Islam for civilization and humanity. This research includes qualitative research in the form of library research, which is descriptive through logical analysis. While the technique used in raising the data is by way of research or library research. study that Islam is a religion that wasathan. Moderate Islam that is reflected in the social organization of diversity in Indonesia has made a valuable contribution to the survival of the national level in particular and the world at large. Evidenced by the dialogue between organizations and religious social cooperation able to become a prototype in the public as a community of Muslims who provide fresh air for a harmonious and peaceful survival in reaching a civilized nation under the auspices of an earthly normative concept. Abstrak: Islam tidak terlepas dari al-Qur‟an dan al-Hadits sebagai pijakan sumber hukum. Namun di sisi lain, Islam distigmakan sebagai agama yang ekstrim, dengan mengatasnamakan agama yang bersumber dari al-Qur‟an dan as-Sunnah. Kajian ini bertujuan untuk mendeskripsikan dan melacak moderasi Islam untuk peradaban dan kemanusiaan.Penelitian ini termasuk penelitian kualitatifdalam bentukpenelitian kepustakaan (Library Research), yang bersifat deskriptif melalui analisis logis.Sementara teknik yang digunakan dalam mengangkat datanya adalah dengan caraBookResearch atau studi kepustakaan.Berdasarkan pada hasil kajian bahwa Islam adalah agama yang wasathan.Islam moderat yang tercermin dalam organisasi sosial keagaman di Indonesia telah memberikan sumbangsih yang berharga bagi kelangsungan hidup bertolerasi di kancah nasional khususnya dan dunia pada umumnya. Terbukti dengan adanya dialog antar organisasi dan kerjasama sosial keagamaan mampu menjadi prototype di kalayak publik sebagai ummatan wasathan yang memberikan angin segar bagi kelangsungan hidup yang rukun dan damai dalam menggapai bangsa yang beradab di bawah naungan konsep normatif yang membumi.